Wind energy, nest success, and post‐fledging survival of Buteo hawks. Issue 7 (18th July 2016) - Kolar, Patrick S.; Bechard, Marc J.
ABSTRACT: Quantifying the rate of turbine collision mortality for raptors has been the primary focus of research at wind energy projects in Europe and the United States. Breeding adults and fledglings may be especially prone to collisions, but few studies have assessed the consequences of increased mortality and indirect effects from this type of development activity on reproduction. We examined the influence of wind turbines and other factors on nest success and survival of radio‐marked juveniles during the post‐fledging period for 3 sympatric breeding Buteo species in the Columbia Plateau Ecoregion (CPE), Oregon, USA. Nest success for ferruginous hawks ( Buteo regalis ) decreased as the number of wind turbines within the home range buffer (32 km 2 ) increased. There was no effect of turbines on nest success for red‐tailed hawks ( Buteo jamaicensis ) or Swainson's hawks ( Buteo swainsoni ). Of 60 nestlings radio‐marked from all 3 species, we found no evidence that any were killed as a result of collisions with wind turbines after fledging. This was likely due, in part, to the limited size of the natal home range and the relatively short duration of the post‐fledging period. However, juveniles of all 3 species hatched from nests in areas of greater turbine density were more likely to die from predation or starvation just after fledging and prior to becoming independent compared to those in areas of lower turbine density. Taken together, these results suggest that wind turbines affected reproductive efforts by all 3 species to some degree, but these effects were greater for ferruginous hawks compared to the other 2 congeneric species. The causes of this negative association are unknown but likely represent some combination of breeding adults being killed from turbine collisions, disturbed from activities associated with the increasing wind energy development in the area, or displaced from portions of their home range to minimize the risk of disturbance or death. The potential for these effects necessitate that planning of future wind energy facilities be considered at larger geographic scales beyond the placement of individual turbines to limit development near raptor breeding areas. © 2016 The Wildlife Society.